2003
DOI: 10.1046/j.1365-2044.2003.02788_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cerebral oxygenation in children undergoing surgical repair of ventricular septal defects

Abstract: SummaryMathematical formulae to calculate body surface area from measurements of height, weight and other parameters date from the late 19th century. Drug doses, fluid therapy, caloric requirements and physiological parameters such as cardiac output, glomerular filtration rate and a variety of respiratory function parameters are all frequently expressed in terms of a body surface area. Body surface area is often used in preference to body mass (weight). However, the original rationale for using body surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
(34 reference statements)
0
8
0
1
Order By: Relevance
“…Table 2 Physiologic data during the study. (11)(12)(13) or jugular venous saturation (18,19) in children (12,13) and adults (11,18,19). Cerebral oxygen metabolism balance is altered at the start of CPB (11,12), recovers during hypothermic CPB (13,18), and is again altered during rewarming (13,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 Physiologic data during the study. (11)(12)(13) or jugular venous saturation (18,19) in children (12,13) and adults (11,18,19). Cerebral oxygen metabolism balance is altered at the start of CPB (11,12), recovers during hypothermic CPB (13,18), and is again altered during rewarming (13,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The value of NIRS-measured haemoglobin oxygenation parameters during CPB has been proposed by several authors (11)(12)(13)(14). Contamination from skull and skin can be a potential confounding factor (24), but a small head diameter and thinner skull and scalp minimizes this effect in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally in support of this, several studies in various models have shown that the use of real-time arteriovenous and near-infrared saturation monitoring and the monitoring of oxygen uptake, venous oxygen tension, and lactic acid production support the safe use of these lower flow rates during bypass [79][80][81][82][83]. The use of real-time NIRS as a trending device is useful in guiding flow rate requirements during bypass and tolerance to temporary low flows required to improve visualization at the surgical field [84][85][86][87][88]. In a practical sense, the perfusionist determines flow rates during cardiopulmonary bypass primarily by patient temperature, anatomic considerations, achievable venous return, and institutional/surgeon preferences, particularly for systemic vascular resistance and mean arterial blood pressure management.…”
Section: Flow Ratesmentioning
confidence: 99%
“…As alterações neurológicas no pós-operatório de cirurgia cardíaca podem ser causadas por alguns fatores como hipotermia e perfusão cerebral inadequada durante a operação e a CEC, tempo de parada cárdíaca, isquemia e hipóxia por embolias gasosas, edema cerebral secundá-rio à retenção hídrica, distúrbios metabólicos como hipoglicemia, hipocalcemia, hiponatremia, acidose e hipomagnesemia 7,8 . Podem manifestar-se das mais variadas formas, com agitação, convulsões, coreoatetose 29 (devido à CEC) e coma.…”
Section: Problemas Neurológicosunclassified